Amphotericin B responsive Scedosporium apiospermum infection in a patient with acute myeloid leukaemia. Issue 1 (January 1996) - Cunningham, R; Mitchell, D C
Abstract : A 71 year old man with newly diagnosed acute myelomonocytic leukaemia developed a soft tissue infection of his foot during his first course of chemotherapy. Scedosporium apiospermum was isolated from the lesion, which resolved rapidly on treatment with intravenous amphotericin B despite being resistant in vitro to this agent. This observation suggests that sensitivity testing of S apiospermum should be interpreted with caution and that clinical response may be a better indicator of outcome.